FTO SUMOylation regulates the differentiation of bone marrow mesenchymal stromal cells in inflammatory bowel disease-induced bone loss - Haoming Wang; Jiandong Guo; Lijun Li; Hongwei Xie; Jiateng Zhang; Wanda Zhang; Ying Liu; Qingliang Ma; Shiyu Wang; Putao Yuan; Zhiwei Jie; Shunwu Fan; et al. (Cell Reports)
Summary: The gut-bone axis is critical for body homeostasis, but bone loss often complicates inflammatory bowel disease (IBD) with unclear mechanisms. Here, we found that IBD mice showed reduced bone formation, with bone marrow mesenchymal stromal cells (BMSCs) favoring adipogenesis over osteogenesis. Altered N6-methyladenosine (m6A) modifications of BMSCs were confirmed in IBD mice, and further investigation revealed that the SUMOylation of FTO was involved. Nude mice with FTO-K216/357/365R mutation exhibited increased bone sizes and volumes versus control mice. Tocilizumab, an interleukin (IL)-6R monoclonal antibody, combined with AAV-FTO-3KR, mitigated bone loss and enhanced bone formation in IBD mice. Our findings reveal that SUMOylation of FTO is involved in the differentiation of BMSCs in mice with IBDs. The outcome could be blocked by redirecting differentiation toward osteoblast treatment with AAV-FTO-3KR and the clinical-stage inhibitor, tocilizumab.